Ensilability and chemical composition of silages made with different mixtures of noni (Morinda citrifolia L.) - Sánchez, Yoandris Pascual; Betancur-Hurtado, Cesar; Botello-León, Aroldo; Pérez-Corría, Kirenia; Ruiz-Corrales, Cristina; Martínez-Aguilar, Yordan (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The ensilability and chemical composition of silages made with different proportions (100:0; 90:10; 80:20; 70:30; 60:40 and 50:50%) of foliage (fresh and pre-wilted) and noni fruit (fresh) was evaluated. Some fermentative patterns of the original forages and the chemical content of the silages were determined. Correlations between the parameters of quality, chemical composition and the fruit levels in the mixture were made and adjusted the same one to polynomial equations. A higher inclusion of fruits with both fresh and pre-wilted foliage of noni decreases the pH and NH3-N Nt-1 in the silage. In addition, the increase in the level of fruit increased the concentration of water soluble carbohydrates (WSC) and the ratio of WSC/PC. Moreover, the pre-wilted foliage increased the dry matter (DM) content and its combination with fruit levels between 30 to 40% decreased the fibrous compounds and crude protein (CP) concentration in the silage. According to a cubic model used, the pre-wilted foliage and fruit proportions showed a higher R2 for DM, neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent-lignin (ADL) and cellulose, while CP and hemicelluloses were higher in the fresh plant material. The results showed that the pre-withered process (foliage) and inclusion levels of 30 and 40% of fruits in the mixture improved the quality of the silage intended for animals.